Complejos turísticos y la calidad de servicios en el cantón Ventanas - Santillan Cabezas, Melissa Andreina (2019)
Within the investigation, the topic of the tourist complexes and the quality of the services in Canton Ventanas is addressed. The tourist complexes are places designed to offer goods and services with the fundamental purpose of satisfying society, a place where they can have fun and relax with their family and friends. Ventanas is the fourth most populated canton of the province of Los Ríos, with a population of 74,100 inhabitants, its extension is 533 km2. It produces products such as corn, which is the livelihood of most of its population, and also produces products such as bananas, rice, cocoa, coffee, soybeans, passion fruit, and shirker. Tourism in the canton is scarce because there are few recreational establishments that offer good quality services and that satisfy their visitors, often its inhabitants have to resort to visiting other places outside their canton to satisfy their main leisure needs. Its main tourist resources are the freshwater rivers that are visited throughout the year by the inhabitants and tourists, especially in winter and during the carnival season.